The HIV Matrix Protein p17 Subverts Nuclear Receptors Expression and Induces a STAT1-Dependent Proinflammatory Phenotype in Monocytes - Renga, Barbara; Francisci, Daniela; D'Amore, Claudio; Schiaroli, Elisabetta; Mencarelli, Andrea; Cipriani, Sabrina; Baldelli, Franco; Fiorucci, Stefano (PLOS ONE, 2012)
Background Long-term remission of HIV-1 disease can be readily achieved by combinations of highly effective antiretroviral therapy (HAART). However, a residual persistent immune activation caused by circulating non infectious particles or viral proteins is observed under HAART and might contribute to an higher risk of non-AIDS pathologies and death in HIV infected persons. A sustained immune activation supports lipid dysmetabolism and increased risk for development of accelerated atehrosclerosis and ischemic complication in virologically suppressed HIV-infected persons receiving HAART. Aim While several HIV proteins have been identified and characterized for their ability to maintain immune activation, the role of HIV-p17, a matrix protein involved in the viral replication, is still undefined. Results Here, we report that exposure of macrophages to recombinant human p17 induces the expression of proinflammatory and proatherogenic genes (MCP-1, ICAM-1, CD40, CD86 and CD36) while downregulating the expression of nuclear receptors (FXR and PPARγ) that counter-regulate the proinflammatory response and modulate lipid metabolism in these cells. Exposure of macrophage cell lines to p17 activates a signaling pathway mediated by Rack-1/Jak-1/STAT-1 and causes a promoter-dependent regulation of STAT-1 target genes. These effects are abrogated by sera obtained from HIV-infected persons vaccinated with a p17 peptide. Ligands for FXR and PPARγ counteract the effects of p17. Conclusions The results of this study show that HIV p17 highjacks a Rack-1/Jak-1/STAT-1 pathway in macrophages, and that the activation of this pathway leads to a simultaneous dysregulation of immune and metabolic functions. The binding of STAT-1 to specific responsive elements in the promoter of PPARγ and FXR and MCP-1 shifts macrophages toward a pro-atherogenetic phenotype characterized by high levels of expression of the scavenger receptor CD36. The present work identifies p17 as a novel target in HIV therapy and grounds the development of anti-p17 small molecules or vaccines.